The Influence of Transformational Leadership Style, Work Stress and Work Discipline on the Performance of Employees at the Nganjuk Agricultural Service Office - Afifah, Rizky Nur (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This For know and analyze Leadership Style Transformational , Stressful Work and Discipline Work On the Performance of Agricultural Service Office Employees Nganjuk . Design/ Methode/Approach: This research uses a quantitative approach based on positivism. The data used in the research is primary data from respondents filling out questionnaires and using the SPSS application for calculations. The population used was all employees and the samples obtained were 85 samples. Result finding: The results of multiple regression analysis show that Ha's test results were accepted, meaning , Leadership Style Transformational (X1), Stress Work (X2) has an effect in a way Partial influential to variable bound (Y) namely Employee Performance , however Discipline Work (X3) no show significant influence .​ It is hoped that this research will be useful to help agencies and can increase readers' insight and knowledge in making decisions. The results of this research indicate that Leadership Style Transformational (X1), Stress Work (X2) and Discipline Work (X3) against performance Nganjuk Regency Agriculture Service employee . In this research, the problem is only limited to predetermined variables which only discuss transformational leadership style, work stress, work discipline on performance at the Agricultural Service